Gold-catalyzed formal cyclisation/dimerization of thiophene-tethered diynes - Tšupova, Svetlana; Hansmann, Max M.; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2017)
A new pathway in dual gold-catalyzed reaction of thiophene-tethered diynes has been identified. A series of fully conjugated alkynyl-substituted benzothiophenes and benzofurans was obtained by a formal cyclisation/dimerization sequence. All the products are fluorescent, owing to their extended conjugation. The mechanistic studies have been carried out, suggesting that gold acetylides take part in this transformation.